Seeking of agriculture information through mobile phone among paddy farmers in Selangor - Ramli, Nor Sabila; Hassan, Md Salleh; Man, Norsida; Abu Samah, Bahaman; Omar, Siti Zobedah; A Rahman, Nur Atikah; Yusuf, Sarina; Ibrahim, Muhamad Shamsul (Human Resource Management Academic Research Society, 2019)
Introduction:Mobile phone is one of the communication tools that have always mattered in many fields included agriculture. The development of the agriculture sector in the rural area is significant to diminish poverty among farmers. Agricultural activities are known to provide opportunities for employment and generating income in the rural area. Poverty can be reduced through adequate investment and improvement in the agriculture sector. Enhancing the use of mobile phone will empower farmers with relevant agriculture information. Thus, agriculture production and profits as well as farmers’ food security and livelihood will increase. Methodology:This study uses a quantitative approach, where an adopted and adapted questionnaire was employed to obtain the data needed. Through purposive sampling, 400 respondents were surveyed. The respondents selected were those who are involved in paddy farming in Selangor. Results: The finding of the study reveals that paddy farmers in Selangor are comfortable using mobile phones in seeking agricultural information. The result for communication appsindicates that WhatsApp is the best choice to get information using a mobile phone as 279 respondents responded they were comfortable using WhatsApp to get and share information through a mobile phone. Whereas, the highest agriculture information the farmers sought are information on pest control, farm safety information, and information on pesticide/weed. Conclusion/Recommendation:Due to the well-received mobile phones usage among farmers, it is recommended that organizations such as the Department of Agriculture and Barat Laut Selangor Integrated Agriculture Development Area (IADA) to improve strategies indistributing information on paddy farming using mobile phones.